Evaluating the Impact of a Workplace Wellness Program in Saudi Arabia: An Intra-Department Study. Issue 9 (September 2019) - Altwaijri, Yasmin; Hyder, Sanaa; Bilal, Lisa; Naseem, Mohammad Talal; AlSaqabi, Dimah; AlSuwailem, Fatima; Aradati, Maggie; DeVol, Edward
Abstract : Objective: There is limited evidence on how workplace health promotion is implemented and evaluated in the Arab countries of the Gulf Cooperation Council (GCC). The present study aimed to improve the overall well-being of employees at a departmental level in a hospital setting in Riyadh, Saudi Arabia. Methods: Using a pre-post longitudinal design, a wellness program was implemented, assessing physical activity, diet, work productivity, absenteeism, workplace satisfaction, and stress. Results: Significant improvement was observed in physical functioning of the employees; with a significant increase in average intake of water/d and fruit consumption, significant decrease in average number of soft drinks consumed/wk, and significant decrease in the days of absence in the last 3 months. Conclusions: There were trends in improvement overall on the wellness measures with significant impact on the physical functioning and dietary habits of the employees.